Associations of birth characteristics with perimenopausal disorders: a prospective cohort study. (9th October 2018) - Gao, M.; Goodman, A.; Mishra, G.; Koupil, I.
Abstract: Perimenopausal disorders (PDs) are prevalent and importantly affect quality of life among middle-aged women. Yet, very little is known about the developmental origins of these disorders. The objective of this study was to investigate the associations of birth characteristics with PDs. This cohort study is based on archived birth records for birth weight and gestational age, and followed prospectively in Swedish inpatient and outpatient registers for 8 years ( n =3212). The main outcomes were menopausal and climacteric states (e.g. flushing, sleeplessness), perimenopausal bleeding and other PDs (e.g. atrophic vaginitis). Cox proportional hazards regression models were used to estimate the hazard ratios (HRs) for three subtypes of PDs separately. During the follow-up, 218 women had PDs, among whom 125 had menopausal and climacteric states, 61 had perimenopausal bleeding and 58 had other PDs as first recorded disorder. Birth weight was linearly associated with incidence rate of menopausal and climacteric states [HR=1.66 per 1 kg increase, 95% confidence interval (95% CI)=1.14–2.41]. Gestational age (rather than birth weight) was associated with incidence rate of other PDs (HR=0.87 per 1 week increase, 95% CI=0.79–0.95). Neither birth weight nor gestational age was associated with perimenopausal bleeding. Similar results were found after adjustment for other early-life and adult socio-demographic characteristics. This observational study provides, for the first time, evidence regarding the developmental origins of PDs. Future research is required to investigate the underlying causal mechanisms, which may shed further light on the etiology of this class of disorders.